The Knowledge Rate Of Premarital Woman About Breastfeeding In Blora City (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2019)
Exclusive breastfeeding has many benefits are like decrease baby mortality, baby morbidity,optimize baby growth, helping development of children's intelligence,etc. Kemenkes RI is targeting Giving ASI Exclusive till 80%, but in the reality in 2015, coverage ASI Exclusive in Central Java just till 61,6%. To increase it’s variable, so one of the step which can be done by health service is giving education for the candidate of brides. The purpose of this research is for knowing that there is an influence of module of dukesi or not with level of knowledge. This research is comparative analytic. Sampling by total sample technique numbered to 30 pairs future brides. Data collection by questionnaires. Data analysis using statistical test. Non parametrik by analysis technique Mann Whitney. The test results Mann Whitney, there is a significant influence between future brides knowledge level who given counseling by using module and not using module by significancy p score amount 0,037. The conclusion is, there is dukesi influence to the level of knowledge from future brides about ASI.